Commissive Act Used in Fatherhood Movie (2021) - Yasikha Caniago; Afriana Afriana (Institut Agama Islam Negeri Palopo, 2022)
The researchers identified types of commissive act that used in Fatherhood Movie that released in June 2021. This research used Yule’s and Searle’s theory to analyse the data. The research was conducted using qualitative research theory by creswell (2017). The researchers used observational technique to collect the data using Sudaryanto (2015). This research got the data from watching Fatherhood movie. From the results of this analysis, the researchers found 15 data divided into 6 types. There are 6 types for offering, 3 types for refusal, 2 types for promising, 2 types for guarantee, 2 types for threatening, and the last 1 type for volunteering. It can be concluded that the most common use of commissive act in the Fatherhood Movie is offering, while the least is volunteering.